Taking Steps: using collaborative group game design to consolidate and evaluate experiences of individual chief complaint-orientated cognitive behavioural therapy for psychosis (C-Co CBTp) in conditions of high security. (26th May 2016) - Slater, Jonathon J. G.; Painter, Glenn
Abstract: Although individual cognitive behavioural therapy for psychosis (CBTp) is a recommended treatment in the UK, studies evaluating participant experiences are limited, particularly in high-security (HS) conditions. Traditional methods of participant evaluation disadvantage HS patients. Individual chief-complaint orientated CBTp (C-Co CBTp), a variant of CBTp, is offered in a HS setting. The paper aimed first, to evaluate participant experiences of individual C-Co CBTp within HS conditions, and second, to evaluate collaborative group game design as a means of evaluating participants' experiences. Collaborative group game design was used as a novel method of participatory action research to evaluate patient and practitioner experiences of C-Co CBTp. Fifteen participants (10 inpatients, five staff) developed a life-size game representing their experiences of C-Co CBTp and offered feedback on the process. The game comprised of 24 squares, each depicting and describing a therapy experience, and a set of game-play cards. Collaborative group game design is a viable means of evaluating participant experiences. Findings corroborate and add to the current evaluation literature. Participants placed particular emphasis on collaboration, the therapeutic relationship, therapy as a nonlinear process and vulnerability and hope.